Reality of Vietnam’s Commercial Bank Performance and Soundness - Nguyen, Thi Canh (University of Economics Ho Chi Minh City, 2023)
This paper employs CAMELS rating system to evaluate the performance and soundness of Vietnam’s commercial banks. Based on the analysis of data from financial statements of the banks in the years 2005/2008–2013, the research results show that the total assets and equity capital of Vietnam’s commercial banks have increased, but their efficiency is not yet high and tends to gradually decrease. The expense-to-revenue ratio was higher than 80% while the return on assets (ROA) ratio remained around 1% and had a tendency to sharply fall to 0.77% and 0.56% in 2012 and 2013 respectively. The return on equity (ROE) ratio, in addition, fell steadily in 2012 (7.42%) and 2013 (5.84%). The findings also indicate that profitability of state-owned commercial banks is higher than that of private joint-stock ones. Additionally, risk degree was high because of a high bad debt (around 4%) and low liquidity (around 90% of loan-to-deposit ratio). In addition to its analysis, the research offers sevaral recommendations that aim at improving banking efficiency and mitigating risk as for Vietnam’s commercial banks.